Psalmberyming in Afrikaans - Van Rensburg, Francois Izak Janse (Verbum et ecclesia, 2006)
The article maps the process by means of which the versification of the Hebrew Psalms in Afrikaans, with its goal of acceptance by the relevant clerical bodies and their ecclesiastical community as a whole, ran its course. The process is illustrated by the history of the two versifications officially commissioned and approved by the mainstream Afrikaans churches, namely those of Totius (professor J D du Toit) and professor T T Cloete, more than half a century separated in time and trend (1937 and 2001 respectively). In view of the fact that both versifiers, as well as professor Lina Spies and dr. Antjie Krog who additionally contributed versifications of a few Psalms, are high profile poets, the evaluation of their work does not only take into account the factor of veracity (compliance with the Hebrew original), but also that of linguistic and stylistic excellence, the Psalms being regarded as poetry.